The integrated STEM teacher identity scale for pre-service teachers: Evidence from Rasch and confirmatory factor analysis - Ahmad Suryadi; Endang Purwaningsih; Amrizaldi; Ahmad Swandi; Abdul Haris (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2026)
Integrated STEM teacher identity is important for preparing pre-service teachers to implement integrated STEM instruction. This study aimed to develop and provide initial validation evidence for the Integrated STEM Teacher Identity Scale for Pre-service Teachers using an exploratory sequential mixed-methods design that combined qualitative interviews, literature review, expert judgment, Rasch analysis, and Confirmatory Factor Analysis. Three experienced teachers who had implemented integrated STEM instruction were interviewed to identify relevant identity dimensions, and based on these findings and the literature, an initial pool of 44 items was developed and reviewed by experts. The first pilot test involved 59 pre-service teachers and was analyzed using Rasch modeling to examine dimensionality, item fit, and reliability, while the second pilot test, conducted after revision, involved 119 pre-service teachers and was analyzed using Rasch modeling and Confirmatory Factor Analysis. The final scale consisted of 28 items across six dimensions: personal experience, self-definition, recognition, competence-performance beliefs, interest, and commitment. The CFA results supported the six-factor model, with acceptable fit indices (RMSEA = 0,067; TLI = 0,905; CFI = 0,917; IFI = 0,919), composite reliability ranging from 0,79 to 0,94, and Cronbach’s alpha ranging from 0,68 to 0,90. Convergent validity was supported for most dimensions, although personal experience and self-definition showed AVE values below the recommended threshold, and the commitment dimension showed relatively low person reliability. Overall, the scale provides promising initial evidence, although further refinement is needed.